Helminth parasites of some freshwater fishes from Baja California Sur, Mexico - Méndez, Oscar; Salgado-Maldonado, Guillermo; Caspeta-Mandujano, Juan Manuel; Cabañas-Carranza, Guillermina (Zootaxa, 2010)
Nine freshwater fish species were sampled from 13 bodies of water in Baja California Sur state, on the Baja California peninsula, Mexico. Twenty-four helminth parasite species of 19 genera and from 13 families were recorded. All are new records for the region, but have been recorded previously in Mexico. No endemic helminth species were identified. Most helminths were larval forms of generalist Nearctic species transported by ichthyophagous birds, in addition to five anthropogenically introduced species. Poeciliid fish are the most widely distributed in the oases and other waters of Baja California Sur, and their helminths are the most common on the peninsula.